Effect of solvent variation on results of antibiotic susceptibility test using the disk diffusion method against Staphylococcus aureus - Habibah, Firda Nurul; Sufa, Hafizah Ilmi; Kurniati, Iis; Rismiarti, Zuri (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2025)
Background Mueller-Hinton agar (MHA) is widely used for disk diffusion tests to assess antibiotic susceptibility in non-fastidious bacteria. The type of water used to prepare the MHA may have affected the test outcomes. Objective This study evaluated the effect of different water types as solvents on the antibiotic susceptibility test results of tetracycline and gentamicin against Staphylococcus aureus. Methods MHA was prepared using four types of water: distilled (control), bottled, reverse osmosis (RO), and municipal tap water (PDAM). Antibiotic susceptibility testing was performed using the Kirby-Bauer disk diffusion method, and data were analyzed using One-Way ANOVA and Tukey’s Post Hoc test. Results The mean inhibition zones for tetracycline were 23.8 ± 0.99 mm (distilled), 23.4 ± 0.37 mm (bottled), 23.0 ± 0.43 mm (RO), and 17.8 ± 1.41 mm (tap), categorized as sensitive except for tap water (intermediate). For gentamicin, the zones were 11.7 ± 0.37 mm (distilled), 12.7 ± 0.77 mm (bottled), 9.8 ± 0.18 mm (RO), and 17.6 ± 1.19 mm (tap), with the first three classified as resistant and tap water as sensitive. The tap water results were significantly different (p<0.05) from those of the other antibiotics. Conclusion The use of non-standard solvents in MHA preparation, particularly tap water, may lead to inconsistent antibiotic susceptibility results. Standardized use of distilled water is recommended to ensure test accuracy and reliability.